Changes in leaf characteristics with tree age in Dryobalanops beccarii dyer in a restored forest of Sarawak, Malaysia - Lapok, Emilla Yastari; Ong, Kian Huat; Keen, John Chubo; King, Jie Hung (Science Publications, 2017)
Study on leaf properties of an endangered dipterocarp tree species, Dryobalanops beccarii, was conducted in a restored forest. The study focused on the morphology, nutrient concentration and gas exchange in well-developed leaves of D. beccarii at different ontogenetic phases. The hypothesis tested that leaf physiological and morphological changes are related to the nutrient concentration level of D. beccarii leaves in each ontogenetic phase. Seedling leaves were small and thin, whereas adult tree leaves were the large and thick. The stomata density per unit was abundant in adult tree leaves as compared to seedlings and saplings leaves. The net photosynthetic rate (Pn), transpiration rate (A) and stomatal conductance (gs) was increased from the seedling phase until the sapling phase, but decreased as the D. beccarii reached the mature phase. Scarce stomata density in seedling leaves contributed to low Pn, A and gs, while sapling leaves recorded opposite results due to abundant stomata density accompanied by highest accumulation of nitrogen (N) content per unit leaf area. The low concentration of nitrogen (N), phosphorus (P) and magnesium (Mg) detracted the gas exchange performance. Hence, changes in leaf morphology and physiology of D. beccarii were affected by the differences in resource used at each tree ontogenetic phase.